1972
DOI: 10.1145/361237.361242
|View full text |Cite
|
Sign up to set email alerts
|

Use of the Hough transformation to detect lines and curves in pictures

Abstract: Public reporting burden for the collection of information is estimated to average 1 hour per response, including the time for reviewing instructions, searching existing data sources, gathering and maintaining the data needed, and completing and reviewing the collection of information. ABSTRACTHough has proposed an interesting and computationally efficient procedure for detecting lines in pictures. In this paper we point out that the use of angle-radius rather than s lope-intercept parameters simplifies the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
2,600
0
59

Year Published

1996
1996
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 5,646 publications
(2,664 citation statements)
references
References 1 publication
5
2,600
0
59
Order By: Relevance
“…In 19 comparison with the traditional method, the new algorithm was more capable of 20 handling with highly noisy data, and could avoid the aliasing problem, i.e., reporting 21 multiple lines instead of single expected line. The results of this study suggested that 22 Introduction 8 Ultrasound imaging has been widely used to assess human muscles in both static and 9 dynamic conditions. In recent years, it has been employed to measure the quantitative information.…”
mentioning
confidence: 85%
See 2 more Smart Citations
“…In 19 comparison with the traditional method, the new algorithm was more capable of 20 handling with highly noisy data, and could avoid the aliasing problem, i.e., reporting 21 multiple lines instead of single expected line. The results of this study suggested that 22 Introduction 8 Ultrasound imaging has been widely used to assess human muscles in both static and 9 dynamic conditions. In recent years, it has been employed to measure the quantitative information.…”
mentioning
confidence: 85%
“…first located the global maximum in the HT accumulator matrix, which corresponded 8 to the most dominant collinear feature points globally, using the standard HT; then the 9 pixels close to the detected line were removed from the edge map, the HT 10 accumulator matrix was calculated again, i.e. revoting, and a new line was detected; 11 the iteration was repeated until the predefined termination conditions were satisfied.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…B-mode and Doppler signals were separated through green channel subtraction. The region of interest and the color scale were then automatically detected using the Hough lines ridge detection algorithm [6]. The target vessel was isolated using a two-pass connected component algorithm.…”
Section: Algorithmmentioning
confidence: 99%
“…To establish correspondence, we compute the center and radius of the best-fit sphere to points sampled on the humeral head using the Hough transform. 15 The Hough Transform yields a score for each of a large number of candidate spheres, centered at different locations and with different radii. The score for a given sphere is proportional to the number of humeral head points through which its surface passes.…”
Section: Validation Of 3d Shape Representationmentioning
confidence: 99%